Regression Models of Soil and Water Losses from Various Erosion Control Measures in Mae Sa Integrated Watershed and Forest Land-use Project, Chiang Mai - Tangtham, Nipon; Korporn, Aphinan (Agriculture and Natural Resources, 1998)
Regression models representing factors influencing soil and water losses from no measures plot (CK), contour bund (CB), hillside ditch (HD), intermittent terrace (IT), and bench terrace (BT) were derived from 305 storm rainfalls collected from 3 replications of 5×20 runoff plots at Mae Sa Integrated Watershed and Forest Land-use Project, Chiang Mai during 1980-1990. Stepwise regression analysis indicate only storm rainfall (Rs) significantly influenced on storm runoff (Qs) in each of all conservation measures with R2 less than 0.5 for either linear or non-linear models. There was no any parameter (Rs, and age of plot, A) meet statistical criteria for Qs in annual prediction basis. In determining sediment concentrations from plot (S), Rs and Qs significantly influenced on strom sediment yield (Ss) either in linear or non-linear multiple regresion but with R2 ranges from 0.3972-0.7267. Age of erosion control measures shows insignificant influence on soil erosion. In annual basis, there was no factor significantly influence on erosion prediction.